2021
DOI: 10.3389/fcell.2021.675411
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M Maintains Naïve Pluripotency of mESCs by Tetraploid Embryo Complementation (TEC) Assay

Abstract: It has been well established that leukemia inhibitory factor (LIF) is essential for maintaining naïve pluripotency of embryonic stem cells (ESCs). Oncostatin M (OSM) is a member of the IL-6 family of cytokines which share gp130 as a receptor subunit, and the OSM-gp130 complex can recruit either LIF receptor β or OSM receptor β. Here we show that OSM can completely replace LIF to maintain naïve pluripotency of ESCs. Mouse ESCs (mESCs) cultured in the presence of LIF or OSM not only express pluripotency genes at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It has been proven that LIF plays a role in maintaining the pluripotency of embryonic stem Life 2023, 13, 2194 2 of 16 cells (ESCs) along with a fellow member of the IL-6 family, Oncostatin M (OSM). It has been shown that ESCs maintain their pluripotency when either the LIF or OSM is bound to the gp130 receptor subunit, essentially demonstrating that the LIF plays a massive role in determining whether ESCs differentiate into more specialized cells or they retain their pluripotency for a longer period of time [2]. This confirms that the LIF is responsible for essential mechanisms during the earliest development of a human embryo.…”
Section: Introduction 1defining the Nature Of Lifmentioning
confidence: 84%
“…It has been proven that LIF plays a role in maintaining the pluripotency of embryonic stem Life 2023, 13, 2194 2 of 16 cells (ESCs) along with a fellow member of the IL-6 family, Oncostatin M (OSM). It has been shown that ESCs maintain their pluripotency when either the LIF or OSM is bound to the gp130 receptor subunit, essentially demonstrating that the LIF plays a massive role in determining whether ESCs differentiate into more specialized cells or they retain their pluripotency for a longer period of time [2]. This confirms that the LIF is responsible for essential mechanisms during the earliest development of a human embryo.…”
Section: Introduction 1defining the Nature Of Lifmentioning
confidence: 84%